The effect of leadership, emotional stability, and expertise marker on swift trust in first aid: a text-vignette study - Brodin, Wilhelm; Fernlund, Fredrik; Prytz, Erik (Frontiers in Psychology, 2025)
Autocratic leadership and emotional stability have been found to evoke more swift trust in a first aid context. However, it is still unknown how markers of emergency response expertise affect swift trust in this context. The current study aimed to partially replicate the effect of autocratic leadership and emotional stability and investigate the effect of an expertise marker on swift trust in first aid. Swift trust was measured in text vignettes of a first aid scenario with a 2×2 design (autocratic leadership and emotional stability versus democratic leadership and emotional instability, and presence versus absence of emergency response expertise marker). The results show an interaction effect between leadership behavior and emotional stability with the expertise marker. This suggests that people giving first aid while wearing an expertise marker are expected to show clear and direct leadership and emotional stability for increased swift trust. The positive effect of autocratic leadership and emotional stability on swift trust was also replicated. Future work should investigate more diverse first aid scenarios that are found in real-life first aid.